2021
DOI: 10.1097/md.0000000000026234
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic complexity of rifampicin-induced coagulopathy in a patient with spontaneous muscle bleeding

Abstract: Introduction: Rifampicin is currently used to treat various bacterial infections, with the most significant application in the treatment of tuberculosis. Dose-independent side effects of the drug can lead to the development of various coagulation disorders, among which disseminated intravascular coagulation is the most dangerous. The mechanism of coagulopathy itself is multifactorial, but it is thought to be mediated by an immune response (formation of antigen-antibody complexes) and consequent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Mecanismele deficitului acestor factori pot fi determinate de hipovitaminoza K și reacțiile imunologice (fig. 1) [13]. Deficitul vitaminei K poate fi cauzat de: micșorarea sintezei vitaminei K de microflora intestinală datorită decomntaminării la administrarea internă a R; inhibarea epoxid-reductazei vitaminei K; stimularea degradării vitaminei K; acțiunii hepatotoxice a R. Suspendarea R și prescrierea preparatelor vitaminei K și plasmei au contribuit la ameliorarea stării pacientului, ce confirm deficitul vitaminei K ca mechanism al coagulopatiei.…”
Section: Rezultate Și Discuțiiunclassified
See 1 more Smart Citation
“…Mecanismele deficitului acestor factori pot fi determinate de hipovitaminoza K și reacțiile imunologice (fig. 1) [13]. Deficitul vitaminei K poate fi cauzat de: micșorarea sintezei vitaminei K de microflora intestinală datorită decomntaminării la administrarea internă a R; inhibarea epoxid-reductazei vitaminei K; stimularea degradării vitaminei K; acțiunii hepatotoxice a R. Suspendarea R și prescrierea preparatelor vitaminei K și plasmei au contribuit la ameliorarea stării pacientului, ce confirm deficitul vitaminei K ca mechanism al coagulopatiei.…”
Section: Rezultate Și Discuțiiunclassified
“…Concomitent hipoalbuminemia poate determina majorarea fracției libere a R cu creșterea toxicității. S-a constatat, că administrarea intermitentă a R datorită activării repetate a sistemului imun poate determina un risc mai mare de dezvoltare a CID, în timp ce pacienții ce administrează zilnic preparatul mai rar vor dezvolta un răspuns imun [7,11,13].…”
Section: Rezultate Și Discuțiiunclassified
“…It is known that bacterial infections usually happen in surgical sites after orthopedic implantation, which has a negative effect on bone regeneration and integration [ 21 , 22 ]. What is worse, it may even lead to surgical failure [ 23 , 24 , 25 ]. It is reported that the infection rate of implanting-related cases is 5% of primary cases and 6% of renovation cases, and has risen significantly to 43% of previous infection cases [ 26 ].…”
Section: Introductionmentioning
confidence: 99%